Ambroxol for neuropathic pain: hiding in plain sight?. Issue 1 (17th January 2023) - Russo, Marc A.; Baron, Ralf; Dickenson, Anthony H.; Kern, Kai-Uwe; Santarelli, Danielle M.
Abstract: Ambroxol is a multifaceted drug with primarily mucoactive and secretolytic actions, along with anti-inflammatory, antioxidant, and local anaesthetic properties. It has a long history of use in the treatment of respiratory tract diseases and has shown to be efficacious in relieving sore throat. In more recent years, ambroxol has gained interest for its potential usefulness in treating neuropathic pain. Research into this area has been slow, despite clear preclinical evidence to support its primary analgesic mechanism of action—blockade of voltage-gated sodium (Nav ) channels in sensory neurons. Ambroxol is a commercially available inhibitor of Nav 1.8, a crucial player in the pathophysiology of neuropathic pain, and Nav 1.7, a particularly exciting target for the treatment of chronic pain. In this review, we discuss the analgesic mechanisms of action of ambroxol, as well as proposed synergistic properties, followed by the preclinical and clinical results of its use in the treatment of persistent pain and neuropathic pain symptoms, including trigeminal neuralgia, fibromyalgia, and complex regional pain syndrome. With its well-established safety profile, extensive preclinical and clinical drug data, and early evidence of clinical effectiveness, ambroxol is an old drug worthy of further investigation for repurposing. As a patent-expired drug, a push is needed to progress the drug to clinical trials for neuropathic pain. We encourage the pharmaceutical industry to look at patented drug formulations and take an active role in bringing an optimized version for neuropathic pain to market.